Audit Quality and Materiality Disclosure Quality in~Integrated Reporting: The Moderating Effect of Carbon Assurance Quality - Patrick Velte (Corporate Social Responsibility and Environmental Management, 2025)
This study concentrates on the link between audit quality and materiality disclosure quality in integrated reporting and the moderating effect of carbon assurance quality. The cross-country study consists of 612 firm-year observations from European and South African listed firms between 2017 and 2022. Regression analyses indicate that audit fees and big four audit firms are positively and significantly related to integrated reporting quality, whereas audit firms as carbon assurors, reasonable assurance level, and reference to international sustainability assurance standards strengthen this link. These findings are robust to several endogeneity and additional analyses. The study mainly contributes to the increasing research on the influence of financial audits on sustainability issues. To the best of our knowledge, this is the first empirical study on the relationship between audit quality and integrated reporting quality, based on materiality disclosure. Moreover, the moderator effect of carbon assurance quality is included as an innovative complementary monitoring factor.
Keywords: 650; audit fees; audit quality; big four audit firm; carbon assurance; integrated reporting; materiality